Determinação experimental e numérica da redução sonora aérea em paredes de alvenaria utilizadas em habitações - Pinto, Rodrigo Barcelos (2011)
In this research some kinds of masonry walls have been used as internal divisions in three Brazilian dwelling buildings to determine the airborne sound reduction, by experimental tests in field and computer simulations. The masonry walls studied are composed by massive bricks, bored ceramic blocks (6 and 4 holes) and structural (7 and 10 MPa), with mortar lining in both sides. The acoustic evaluations, in field, were accomplished according to the international rules ISO 140 part 4, ISO 717 part 1 and ISO 354. The determination of the airborne sound reduction among places it was accomplished from a direct and indirect sound transmission of constructive elements of the edifications, according to the EN 12354 rule part 1 and using a commercial computer program. The mainly results of this research showed the weighted values of the level standard difference (DnT,w) vary from 37 to 44 decibels to the evaluated walls. It was also observed the difference of 2 dB among the weighted values of the level standard difference (DnT,w) and the apparently sound reduction (R w). Almost all the masonry walls evaluated reached the minimum recommended values by the NBR 15575. In general, it happened a relation between the experimental results and the computer simulations, mainly with the weighted values relation and the isolation curves of the structural masonry walls. The computer simulation of the airborne sound transmission can be a good project tool, besides the initial datas don t represent properly the masonry material components evaluated, due to the national datas more complete and precise.